An Estimation of the Cost Function and The Size Economics of Autumn Sugar Beet in Al-Ghab/ Syria (Damascus University Journal of agriculture sciences, 2024)
This study was conducted on a sample of Sugar Beet farmers "Autumn period" in Alghab/Syria region for the 2018/2019 season, depending on a field questioner targeted a random sample of 80 farmers. The research aimed to estimate the total cost function of autumn Sugar Beet, and to measure its optimal economic scales.The Results showed that farming of Sugar Beet in the study sample run place in the stage of economic production, where the cost elasticity reached 0.87, which indicates that farms of sample are within the stage of increased return of scale. From other hand farmers generally achieved only 84.6% of the optimal production amount in the short term, estimated at 51850 kg/farm, equivalent to 5237.4 kg/dunum and 66.6% of the maximizing production level, this mainly due to the low efficiency of the use of productive factors. In the long term, the optimal production amount was estimated at (5116.3) kg/dunum, which was about 15.5% higher than the actual production amount. The optimal area in the long term was (16.9) dunums, 1.7 times compared to the actual average area. Accordingly, the 7-dunum holdings arethe most economically efficient, their ratio estimated at 16.3% of total holdings. They achieved the optimal production scale and minimize the long-term cost average to 10.1 SP/kg, it is much less than the short-term cost average  that estimated at 20.9 SP/kg.
Keywords: Autumn Suger Beet Production; Cost Function; Economic Scale